1990
DOI: 10.1577/1548-8675(1990)010<0106:teoiho>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Illegal Harvest on Recreational Fisheries

Abstract: The degree of compliance with a fishing regulation can have a significant impact on the regulation's effectiveness. In this paper, we use a yield‐per‐recruit simulation model to evaluate the effect of poaching on legal harvest in sport fisheries. Two types of illegal harvest were considered: harvest of fish below the legal size limit and harvest of fish from catch‐and‐release fisheries. The results depict the degree of reduction in legal harvest in minimum‐size fisheries with 0‐100% (in 10% increments) illegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 8 publications
1
45
0
Order By: Relevance
“…For example, Pierce and Tomcko [7] suggested that much of the 29% non-compliance rate for five Minnesota lakes was due to a lack of awareness of the applicable regulations, while Page and Radomski [8] found that fishers less aware of the regulations were more likely to be non-compliant among multiple fisheries. Fisher attitudes can also affect compliance behaviour, with even low levels of noncompliance potentially undermining the management regime's effectiveness [9,10]. Negative attitudes may also reflect fishers' perceptions of the legitimacy of key regulations, which can affect the probability of non-compliant behaviour [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pierce and Tomcko [7] suggested that much of the 29% non-compliance rate for five Minnesota lakes was due to a lack of awareness of the applicable regulations, while Page and Radomski [8] found that fishers less aware of the regulations were more likely to be non-compliant among multiple fisheries. Fisher attitudes can also affect compliance behaviour, with even low levels of noncompliance potentially undermining the management regime's effectiveness [9,10]. Negative attitudes may also reflect fishers' perceptions of the legitimacy of key regulations, which can affect the probability of non-compliant behaviour [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Biological impacts range from declines in genetic diversity (e.g., large-tusked elephants; Okello et al 2008) and species richness to changes in community composition and ecosystem services (e.g., Pauly et al 2002;Pitcher et al 2002;Edirisinghe 2003). Economically, illegal resource use can provide alternative livelihood strategies to marginalized people and windfall profits to poachers of prized species (Pratt et al 2004;Yonariza & Webb 2007;Tacconi 2008), but legitimate resource users can suffer significant revenue losses as a result of illegal use of resources (Gigliotti & Taylor 1990;Gutierrez-Velez & MacDicken 2008). Socially, illegal resource use can reflect and further exacerbate differences in access to resources.…”
Section: Introductionmentioning
confidence: 99%
“…Although anglers may have diverse motives for spending their leisure time angling, many of them want to bring fish home from a fishing trip in order to be satisfied (Gigliotti and Peyton, 1993). Since the public demand for angling frequently seems to outweigh the biological limits of many fish populations (Espegren et al, 1990;Gigliotti and Taylor, 1990), there is a call for restricted fishing in a number of waters.…”
Section: Introductionmentioning
confidence: 99%